Предмет: Математика,
автор: dufrtcutu87755
упростите выражение 6*(0,4-3)-4,5*(х+2) если: х= -1 2/7
Ответы
Автор ответа:
0
= 2,4 - 18 - 4,5х - 9 = - 4,5х - 24,6
если х = - 1 целая 2/7 = - (1*7+2)/7 = - 9/7
- 4,5 = - 45/10 = - 9/2 - сократили на 5
- 4,5х - 24,6 = (-9/2) * (-9/7) - 24,6 = 81/14 - 24 6/10 = 5 11/14 - 24 3/5 = - (24 42/70 - 5 55/70) = - (23 112/70 - 5 55/70) = - 18 57/70
Ответ: - 18 целых 57/70.
если х = - 1 целая 2/7 = - (1*7+2)/7 = - 9/7
- 4,5 = - 45/10 = - 9/2 - сократили на 5
- 4,5х - 24,6 = (-9/2) * (-9/7) - 24,6 = 81/14 - 24 6/10 = 5 11/14 - 24 3/5 = - (24 42/70 - 5 55/70) = - (23 112/70 - 5 55/70) = - 18 57/70
Ответ: - 18 целых 57/70.
Похожие вопросы
Предмет: Биология,
автор: lianahumaidova92
Предмет: Математика,
автор: Sofaaaa13
Предмет: ОБЖ,
автор: Аноним
Предмет: Математика,
автор: sepochka06
Предмет: Математика,
автор: LadySmail